PROSEDUR PEMERIKSAAN MRI BREAST PADA PASIEN KANKER PAYUDARA DI INSTALASI RADIOLOGI RSUP FATMAWATI - Nur'aini, Istiqomah; Anwar, Khairil; Apriantoro, Nursama Heru (Integrative Perspectives of Social and Science Journal, 2026)
Abstract : Background Breast MRI is an imaging modality with high sensitivity for detecting breast cancer. At the Radiology Department of Fatmawati General Hospital, an additional sequence, VIBRANT (Volume Imaging for Breast Assessment), is used. This sequence is an axial 3D T1-weighted fat-saturated sequence performed dynamically after the administration of gadolinium-based contrast media. Objective This study aims to determine the breast MRI examination procedure and the role of the VIBRANT dynamic sequence in breast cancer patients. Methods This study used a qualitative method with a case study approach conducted in January 2026. Data were collected through observation, interviews, documentation, and literature review. Data analysis included data reduction, data presentation, and conclusion drawing. Results and discussion The examination was performed in prone position, feet first, using pre-contrast and post-contrast sequences including 3D Axial VIBRANT FLEX+C. This sequence provides high spatial resolution and enables clearer visualization of lesion morphology. Conclusion The VIBRANT dynamic sequence allows temporal evaluation of enhancement and produces kinetic curves that play an important role in differentiating benign and malignant lesions.